2021
DOI: 10.3389/fnagi.2021.677090
|View full text |Cite
|
Sign up to set email alerts
|

Screening Tools and Assessment Methods of Cognitive Decline Associated With Age-Related Hearing Loss: A Review

Abstract: Strong links between hearing and cognitive function have been confirmed by a growing number of cross-sectional and longitudinal studies. Seniors with age-related hearing loss (ARHL) have a significantly higher cognitive impairment incidence than those with normal hearing. The correlation mechanism between ARHL and cognitive decline is not fully elucidated to date. However, auditory intervention for patients with ARHL may reduce the risk of cognitive decline, as early cognitive screening may improve related tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 128 publications
(129 reference statements)
0
3
0
Order By: Relevance
“…Auditory event-related potentials have shown significant abnormalities in both amplitude and latency in individuals living with Alzheimer’s disease and mild cognitive impairment. 28 , 29 , 51 Specifically, a meta-analysis conducted by Tarawneh et al showed the promising role of these potentials (eg, P300) in discriminating between those at higher risk of cognitive decline from normal-ageing individuals. 29 Biomarkers of cognitive impairment may also be reflected in clinical measures of listening effort (eg, pupillometry).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Auditory event-related potentials have shown significant abnormalities in both amplitude and latency in individuals living with Alzheimer’s disease and mild cognitive impairment. 28 , 29 , 51 Specifically, a meta-analysis conducted by Tarawneh et al showed the promising role of these potentials (eg, P300) in discriminating between those at higher risk of cognitive decline from normal-ageing individuals. 29 Biomarkers of cognitive impairment may also be reflected in clinical measures of listening effort (eg, pupillometry).…”
Section: Discussionmentioning
confidence: 99%
“…Two systematic reviews have identified the use of auditory event-related potentials as biomarkers for cognitive impairment and Alzheimer’s disease. 28 , 29 Auditory-event-related potentials (eg, P200; P300) were shown to be valuable biomarkers of Alzheimer’s disease, and have the potential to be integrated as a complementary assessment as part of a clinical neuropsychological test battery. 28 An investigation into routine clinical practice is needed to determine the effectiveness of current measures and assess the practicality of using biomarkers in clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ARHL has been associated with social isolation and depression, and it has been recognized as a modifiable risk factor for dementia (Livingston et al, 2017(Livingston et al, , 2020. However, the mechanisms that relate to hearing loss and cognitive decline are complex and still under research (Yue et al, 2021).…”
Section: Introductionmentioning
confidence: 99%